O imaginário social na sociologia brasileira contemporânea (1984-1993) - Rodrigues, Francisco Xavier Freire (MÉTIS: HISTÓRIA & CULTURA, 2011)
VERLINDO, Jorge Augusto Silveira. Caxias do Sul: Educs, 2004. 129 p.